Profil Bakteri Patogen dan Kepekaannya pada Pasien Ventilator Associated Pneumonia dengan Infeksi COVID- 19 di Rumah Sakit UKRIDA¬ - Jeremy Christopher; Ade Dharmawan; Donna Mesina Pasaribu; Nicolas Layanto (Jurnal Kesehatan Andalas, 2022)
The use of ventilators during the COVID-19 pandemic has increased the incidence of Ventilator-Associated Pneumonia (VAP). This is accompanied by a trend of antibiotic resistance resulting from irrational use. The emergence of multi-drug resistant (MDR) bacteria during the pandemic presents a challenge due to limited antibiotic options. Objective: To determined the pathogenic bacterial profile and antibiotic susceptibility in Ventilator Associated Pneumonia (VAP) patients with COVID-19 infection. Methods: This is a descriptive cross-sectional study with a retrospective approach using secondary data from the medical records of UKRIDA Hospital patients from January 2021 to August 2021. Results: Most of the study sample had characteristics of being male (71.9%), aged 25-64 years (78.1%), overweight (40.6%), and hypertension (40.6%) as the comorbid. Gram-negative bacteria is the pre-dominated bacteria in this study, with Acinetobacter baumannii, Klebsiella pneumoniae, and Stenotrophomonas maltophilia being the most isolated bacteria. Antibiotics such as colistin still showed good susceptibility to Acinetobacter baumannii and Klebsiella pneumoniae, with 75% and 90% sensitivities, respectively. Antibiotics such as linezolid, tigecycline, and gentamicin-synergy still showed (100%) sensitivity to all Gram-positive bacteria. Conclusion: The discovery of MDR bacteria in patients with VAP and the limited availability of susceptible antibiotics highlights the importance of conducting antibiotic resistance surveillance and infection control, especially in the era of COVID-19.Keywords:  antibiotic susceptibility, bacteria profile, COVID-19, VAP